Rainbows of Different Order in Water Droplets and Glass Beads - Holovatsky, Volodymyr (Wolfram, 2022)
A single reflection of sunlight inside a falling raindrop produces the primary rainbow. Double reflection gives rise to the secondary rainbow. This Demonstration calculates the parameters for rainbows of the first six orders. You can follow the rays as they are refracted and reflected in water droplets and glass beads to form rainbows of different order. You can move the relative position of the white light source using the locator.
Keywords: Rainbow